Attachment style consistency across different types of relationships - Jelić, Margareta; Kamenov, Željka; Cokarić, Ines (2006)
The aim of our study was to assess the consistency of attachment styles across romantic relationships, friendships and family relationships with respect to participants' age and gender. The sample consisted of 210 undergraduate students of the University of Zagreb and 219 adults. Overall, 174 males and 255 females participated in the study. The shortened version of Brennan’ s The Experiences in Close Relationship Inventory was applied as a measurement of attachment in romantic relationships (Kamenov & Jelić, 2003). In order to assess the level of attachment toward other objects (friends and family members), the instrument was slightly modified. The results show that the attachment style significantly differs depending on the kind of close relationship. Correlation coefficients between the attachment styles in different relationships show that the only relatively consistent style is secure attachment, while all other styles (preoccupied, dismissive and fearful) are not.
Projekt MZOS
ENG